1973
DOI: 10.1136/gut.14.4.300
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preserving antral innervation and of a pyloroplasty on gastric emptying after vagotomy in man

Abstract: SUMMARY A prospective randomized trial of 40 duodenal ulcer patients is reviewed. The patients had one of four operations (selective vagotomy, proximal gastric vagotomy, selective vagotomy plus pyloroplasty, or proximal gastric vagotomy plus pyloroplasty). The gastric emptying of a hypertonic fluid meal was assessed before and three to four months after operation. Selective vagotomy without a drainage procedure results in gastric retention and should no longer be considered as a method of treatment for duodena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2
2

Year Published

1974
1974
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(42 citation statements)
references
References 17 publications
3
35
2
2
Order By: Relevance
“…They explained their finding by a defect in receptive relaxation of the stomach due to visceral neuropathy secondary to malnutrition (Clarke and Alexander-Williams, 1973) as well as reduced ganglion plexuses in the intestine (Viteri and Schneider, 1974). These results are in disagreement with the present study, yet the studies showing reduced ganglion plexuses in the intestine did not discuss the intrinsic stomach innervations and thus should not be relied upon in explaining the delayed GET.…”
Section: Discussioncontrasting
confidence: 57%
“…They explained their finding by a defect in receptive relaxation of the stomach due to visceral neuropathy secondary to malnutrition (Clarke and Alexander-Williams, 1973) as well as reduced ganglion plexuses in the intestine (Viteri and Schneider, 1974). These results are in disagreement with the present study, yet the studies showing reduced ganglion plexuses in the intestine did not discuss the intrinsic stomach innervations and thus should not be relied upon in explaining the delayed GET.…”
Section: Discussioncontrasting
confidence: 57%
“…The gastroduodenal junction (GDJ) plays an important role in regulating gastric emptying (Clarke & Williams, 1973;Aeberhard & Walther, 1978;Hinder & Bremner, 1978;Miller, Kauffman, Elashoff, Ohashi, Carter & Meyer, 1981;Hinder & SanGarde, 1983;Schulze-Delrieu & Brown, 1985). As the cineradiographs of Code and colleagues show (Smith, Code & Schlegel, 1957;Carlson, Code & Nelson, 1966) peristaltic contractions originating in the corpus spread aborally sweeping chyme towards the pylorus.…”
Section: Introductionmentioning
confidence: 99%
“…At the Gastric Follow-up Clinic, symptoms suggestive of gastric retention, such as vomiting and flatulence, have been less common after HSV than after TV or SV with a drainage procedure. Finally, studies of gastric emptying of fluids [9,32,62] and of food-and-barium [56,66,77] have revealed no evidence of gastric stasis in man after HSV, whereas complete gastric vagotomy without drain age frequently produces gastric stasis in man [10,50] and in experimental animals [2,70], Regulation o f gastric emptying. Although HSV does not produce gastric retention, the pattern of gastric emptying of fluids is altered.…”
Section: Gastric Emptying and Side Effects After Vagotomymentioning
confidence: 99%
“…HSV keeps intact both the terminal antrum, which mills and grinds solids and controls their emptying [8,11], and the pyloric sphinc ter, which helps to regulate gastric emptying and to prevent reflux of duode nal content into the stomach [9,19,34], In contrast, both the terminal antrum and the pylorus are sacrificed in the course of truncal or selective vagotomy with pyloroplasty. The average length of pre-pyloric stomach which remains innervated in HSV is about 6.5 cm [44], The anatomical landmarks provided by the nerves of Latarjet govern the extent of gastric denervation in HSV, whereas in the closely similar operation of parietal cell vagotomy (PCV) [1], the precise extent of the antrum is 'mapped' at the time of operation by means of a pH probe.…”
Section: Definitionsmentioning
confidence: 99%